Development Of Engineering Students' Drawing Skills For Field-Related Drawing Projects - Kahharov Abdurakhim Abdubannaevich; Ogalikov Mirzaakbar Botiralievich (Periodica Journal, 2023)
The article provides suggestions for using SAD design systems as a tool for students to visualize complex drawings used in the technical field
Keywords: computer graphics; modern computer technologies; imagination